2008
DOI: 10.3184/030823408x390208
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 5-alkylidenepyrazol-4(1H)-ones and 3-amino-6-aryl-5-cyano-pyridazine-4-carboxylates from arenealdehyde thiosemicarbazones and unsaturated 1,2-diesters

Abstract: The reaction of arenealdehyde 4-phenylthiosemicarbazones 1a-f with dimethyl ethynedicarboxylate (6) gave methyl [3-aryl-4-oxo-1-(phenylthiocarbamoyl)-4,5-dihydro-1H-pyrazol-5-ylidenelethanoates 10a-f in 73-79% yield, while, by reaction with diethyl (E)-2,3-dicyanobutenedioate (7), compounds 1a-f are transformed into ethyl [3-aryl-4-oxo-1-(phenylthiocarbamoyl)-4,5-dihydro-1H-pyrazol-5-ylidenelcyanoacetates 15a-f (54-61%) and ethyl 3-amino-6-aryl-5cyanopyridazine-4-carboxylates 24a-f (22-26%). Rationales for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 41 publications
0
20
0
2
Order By: Relevance
“…Compounds 4a , 4b , 4c , 4d , 4e , 4f , 4g , 4h , 4i , 4j , 4k , 4l , 4m , 4n , 4o , 4p , 4q , 4r may react either with their sulfur atom, N 2 or N 4 as nucleophilic sites. On the other hand, it has been reported that the azomethine carbon and N 2 of 1 had taken part in the heterocyclization . The methine carbon of 4 had to act as a nucleophile in the sense of an “umpolung” .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds 4a , 4b , 4c , 4d , 4e , 4f , 4g , 4h , 4i , 4j , 4k , 4l , 4m , 4n , 4o , 4p , 4q , 4r may react either with their sulfur atom, N 2 or N 4 as nucleophilic sites. On the other hand, it has been reported that the azomethine carbon and N 2 of 1 had taken part in the heterocyclization . The methine carbon of 4 had to act as a nucleophile in the sense of an “umpolung” .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been reported that the azomethine carbon and N 2 of 1 had taken part in the heterocyclization . The methine carbon of 4 had to act as a nucleophile in the sense of an “umpolung” . Thus, several options for interaction between 4a , 4b , 4c , 4d , 4e , 4f , 4g , 4h , 4i , 4j , 4k , 4l , 4m , 4n , 4o , 4p , 4q , 4r and 2 may be expected as will be outlined later.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl [3‐aryl‐4‐oxo‐1‐(phenylthiocarbamoyl)‐4,5‐dihydro‐pyrazol‐5‐ylidene]ethanoates were formed from the reaction of arenealdehyde 4‐phenylthiosemi‐carbazones with dimethyl acetylenedicarboxylate (DMAD, 2 ) , whereas 1,2,4‐triazepine‐3‐thiones 4a , 4b , 4c and 5a , 5b , 5c , 5d were formed via conventional and microwave irradiation of 4‐substituted thiosemicarbazides 1a , 1b , 1c and 2,4‐disubstituted thiosemicarbazides 3a , 3b , 3c , 3d with DMAD, 2 (Scheme ) .…”
Section: Introductionmentioning
confidence: 99%
“…A novel and a efficient procedure for the synthesis of thiosemicarbazones has been achieved via a multicomponents and catalyst‐free reaction of phenyl or p ‐ chlorophenyl isothiocyanate, hydrazine, and aldehydes or ketones [33]. Besides, thiosemicarbazones are versatile building blocks in the synthesis of densely substituted heterocycles [34–40]. It has been reported earlier that, isatin‐3‐thiosemicarbazones were cyclized to 5 H ‐ as ‐triazino[5,6‐ b ]indole‐3‐thiones in aqueous K 2 CO 3 [41–43].…”
Section: Introductionmentioning
confidence: 99%